The R book - Jones, Elinor (Associate Professor); Harden, Simon; Crawley, Michael J. (John Wiley & Sons Ltd, 2023)
"The R language is recognized as one of the most powerful and flexible statistical software packages, enabling users to apply many statistical techniques that would be impossible without such software to help implement such large data sets. R has become an essential tool for understanding and carrying out research. This edition introduces the advantages of the R environment, in a user-friendly format, to beginners and intermediate users in a range of disciplines, from science and engineering to medicine and economics. The format enables it to be either read as a text, or dipped-into as a reference manual. This third edition: Uses RStudio, instead of native R, which provides a far more user-friendly environment for those new to R Revised to account for the evolution of R over the past seven years including new developments and modern teaching methods Takes readers from a starting point of no knowledge of R or programming in general, and very little knowledge of statistics, through to advanced techniques Provides a comprehensive introduction to most areas of statistics used by non-statisticians, with minimal mathematics Explains concepts and how to implement them in R with in-depth discussion on how to interpret the resulting output Contains a large number of worked examples in R Companion website available with downloadable datasets, slides and other teaching materials Introduces modern ideas in handling data in R, e.g. the tidyverse. Features full colour text and extensive graphics throughout Features a fully revised and updated bibliography and reference section."--